Analisis Penentuan Harga Pokok Produksi Kaos Pada AZKA Konveksi Nganjuk - Tohari, M.Taufik; Fauji, Diah Ayu Septi; Purnomo, Hery (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2021)
. This analysis aims to find out how much difference and influence the Cost of T-shirt production issued by Azka Convection each production using the Full Costing method. The elements contained in this study are The Cost of Production and The Cost of Goods Sold. This study uses primary and secondary data. Our primary data is obtained by conducting a survey directly to the owner's place of business in order to obtain the correct and correct data. While the secondary data we get from the owner's document archive about sales and production reports. Quantitative descriptive techniques became the approach we used in this study. This research has several problems that must be analyzed, namely (1) How Azka Convection and Sablon determine the Cost of Production so far (2) Whether the determination of the Cost of Production carried out by Azka Convection and Sablon is good in accordance with management science (3) How the calculation of the cost of production is effective and can produce optimal profit Conclusion of the results of this analysis is (1) The owner has not included some costs included in the kat egori overhead to the cost of production (2) The owner in determining the Cost of Production has not shown a reasonable Cost of Production and has not been in accordance with the management principles commonly used (3) Preparation of the Cost of Production that should be done is to use the full coasting method.